ADS Score as a Novel Predictor of Outcomes in Patients Who Underwent Percutaneous Coronary Intervention - Zhang, Wen-Jing; Liu, Gang-Qiong; Shangguan, Jia-Hong; Zhu, Xiao-Dan; Wang, Wei; Guo, Qian-Qian; Zhang, Jian-Chao; Wang, Kai; Liu, Zhi-Yu; Song, Feng-Hua; Fan, Lei; Li, Ling; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objectives: A novel AFR–Alb-derived neutrophil/lymphocyte ratio (dNLR) score (ADS) were reported to associate with clinical outcome in various malignancies, However, the relation between the ADS score and outcomes in coronary artery disease (CAD) patients after percutaneous coronary intervention (PCI) has not been investigated. Methods: 3561 patients were divided into 2 groups according to ADS score: Low group (ADS score<2; n = 2682) and High group (ADS score≥2; n = 879). Overall, there were 133 all-cause mortality (ACM) during the following up. The incidence of ACM in the low group is 2.7% (72/2682) and high group is 6.9% (61/879). The ACM incidence was significantly higher in high group compared to that in the low group (P<0.001). Cardiac mortality (CM) occurred in 82 patients: 44(1.6%) in the low group and 38 (4.3%) in the high group. There was significant difference in the CM incidence between the low group and high group (P<0.001). Major adverse cardiovascular and cerebrovascular events (MACCEs) occurred in 520 patients: 366 (13.6%) in the low group and 154 (17.5%) in the high group. There was significant difference in the MACCEs incidence between the low group and high group (P=0.005). Major adverse cardiovascular events (MACEs) occurred in 395 patients: 281(10.5%) in the low group and 114(13.0%) in the high group. There was significant difference in the MACEs incidence between the low group and high group (P=0.041). The multivariate Cox proportional hazards model showed that ADS score was independently correlated with the ACM (adjusted HR = 2.031 [1.357-3.039], P=0.001); CM (adjusted HR = 1.883 [1.127-3.147], P=0.016); MACCE (adjusted HR = 1.352 [1.096-1.668], P=0.005) and MACEs (adjusted HR = 1.260 [0.987-1.608], P=0.063). Conclusion: The present study indicated that the ADS score was associated with long-term mortality, the MACCEs and the MACEs in CAD patients underwent PCI. Keywords: ADS score; Mortality; Major adverse cardiovascular and cerebrovascular events; Major adverse cardiovascular events; Coronary artery disease; Percutaneous coronary intervention